The Reconstruction of Identity Among Women Displaced by the War in Ukraine - Andrea Preissová Krejčí (Kulturní Studia)
In the Czech Republic, there is regularly updated quantitative data on temporary protection holders from Ukraine, which gives us a fairly good overview of their age, gender or economic activity. However, it does not allow us to understand the complexity of the processes and changes taking place in the lives of individual refugees. We therefore focused our attention on the stories of women who fled the war in Ukraine and who found refuge in the Czech Republic. Using qualitative research methods, we recorded and analyzed 15 narratives in which we trace the transformation of the identity of the female narrators, consisting in the deconstruction of their existing identity—national (e.g., related to the Russian language), social (related to education and occupational prestige) and class (related to economic status) and the construction of a new identity of a refugee. We identify aspects of this new identity that enable refugees to experience feelings of acceptance and belonging in their new society, from newly constructed social networks and community life to support in their current place of residence provided by work colleagues, neighbours or others who help them adapt to their new environment and life roles.